Methods and Principles of the Activity of the Subjects of Administrative and Legal Relations in the Urban Planning Area - Ye. A. Neborskyi (Law and Safety)
It has been stated that state policy in the field of construction should have a complete toolkit – a system of means for transferring decisions, tracking their implementation, adjusting plans and measures, attracting the necessary material and human resources, evaluating the implementation of the policy.